Analisis Faktor Penyebab Kesulitan Belajar pada Keterampilan Membaca Pemahaman di Kelas V SDN Purworejo 02 - Falentina Rizki Nurul Fatimah; Tyasmiarni Citrawati (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This research aims to describe the forms of reading comprehension difficulties and the factors that cause difficulties in learning to read comprehension for fifth grade students at SDN Purworejo 02. This research uses qualitative methods with a case study design. The subjects in this research were 1 class V teacher, 3 class V students, 3 friends of class V students, 3 guardians of class V students who were selected using purposive sampling. Data collection techniques in this research include observation, interviews, and documentacion. The data analysis technique in this research uses Miles and Huberman with stages of data reduction, data presentation, and drawing conclusions. Testing the validity of the data in this research uses triangulation and member check. The results of this research include: (1) difficulty understanding the content of the reading because students have limited vocabulary such as students not knowing many words (2) difficulty concluding the reading due to not understanding the content of the reading. (3) there are four factors that cause difficulties in learning to read comprehension, including interest factors, intellectual intelligence factors, school environmental factors, and family environmental factors